Mekanisme Penetapaii Kebijakan Pengupahan di Indonesia: Suatu Tinjauan Perbandingan Hukum - uwiyono uwiyono (Jurnal Hukum IUS QUIA IUSTUM, 2001)
At the praxis level, the Indonesian labor relations have not been reaching a coalition stage. Therefore democracy at work should be developed in order to prevent the industrial relations from adversarial one. There are some kinds of workerparticipation to improve the relationship between the labor and the laborer, such as peacefull collective bargaining, Works Council or Board of Directors involvement arid also Employee stock ownership plan. This kind of partnerships will createa democratic treatment for any labor issues in Indonesia.